Analisis kinerja keuangan Bank BCA Syariah Berdasarkan Return on Equity (ROE) periode 2020–2024 - Rahma, Anida Salsabila; Aisyah, Esy Nur (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the financial performance of BCA Syariah Bank during the 2020–2024 period, focusing on the Return on Equity (ROE) ratio as the primary indicator of profitability. The analysis employs a financial ratio approach based on data obtained from annual reports and the bank’s official publications. The results show that BCA Syariah’s ROE experienced fluctuations over the five-year period, influenced by changes in net profit, capital structure, and operational cost efficiency. The increase in ROE in 2024 indicates improved efficiency and strengthened financing strategies implemented by the bank. These findings reaffirm that ROE serves as an effective performance evaluation tool in assessing the bank’s ability to generate profit relative to its equity. This research is expected to contribute to the development of Islamic banking performance studies and provide empirical reference for future research.